Complete mitochondrial genome of the Sakhalin nine-spined stickleback Pungitius tymensis (Gasterosteiformes, Gasterosteidae) - Shikano, Takahito; Guo, Baocheng; Merilä, Juha Kari Kristian (Mitochondrial DNA Part B, 2017)
Peer reviewed